(untitled) (Research, Society and Development, 2022)
Lakes formed in open pit mines are suitable habitats for benthic organisms, which are be used to indicate the quality of such water bodies. This study aimed to analyze the benthic community of macroinvertebrates in an artificial lake of a mined area in the process of environmental recovery. Two samplings were accomplished, in which 10 points were arranged at two different distances from the shore, the substrate was revolved for three minutes and collection using a dip net, totalizing one hour of sampling effort. The analysis was based on the attributes of richness (using Bootstrap and Chao1), abundance, diversity (Shannon-Weaver) and environmental quality of the lake (BMPM). A total of 786 individuals belonging to 24 families were sampled. The estimated richness for the area was 24 and 25 families and the samples covered between 92% and 98% of these. Chironomidae (n = 363), Libellulidae (n = 99) and Culicidade (n = 85) were the most abundant. Statistical differences was observed in the diversity and total abundance values between the samples (t = 3.027; p<0.005 and t=1.318; p<0.01, respectively), with higher values in spring. The quality of the lake was categorized as doubtful according to the BMWP’ index for both samplings, demonstrating that the lake is compromised, although the area is in the process of recovery, most abundant families are atypical of polluted areas. The study indicates the importance of biomonitoring in supervising environmental conditions and in creating recovery measures in degraded environments.